PERAN MEDIA KOMUNIKASI DALAM TRANSFER TEKNOLOGI MENDUKUNG PENGEMBANGAN TAMAN AGROINOVASI DI KALIMANTAN BARAT - Kilmanun, Juliana C; Serom, Serom (Faculty of Agriculture, Janabadra University, 2018)
The success of an innovation agricultural technology determined by how a lot oftechnology it was adopted and used by user of the technology. So that that technology can beÂ used by the user so the factor that is very important is that technology known andÂ acknowledged by user of the technology. This study examines the role of mediaÂ communication in transferring technologies in the garden of âagro-innovation westÂ Kalimantanâ. The methodology used is descriptive. The results are that media is aÂ communication that most attractive to is leaflets, the visit roomy / counseling and training. 1.Â a medium of communication play an important role in the acceleration of transferringtechnologies, 2. Form of media communication should be adapted to the request farmersÂ because of its effect in adopting technology especially technological innovations in theÂ garden of agro innovation. 3 . Form of media most attractive to farmers is: 30 percent fromÂ the leaflets, a medium of communication in the form of a visit roomy / information ( 23,33Â percent ) and training of 16.67 percent ) , TV live as much as 13,33 percent, radio broadcastsÂ 10 percent kilometers long percent and brochure